Socio-Demographic Differences in Emotional Empathy, Psychological resilience, and Quality of Life among Individuals with Obsessive Compulsive Disorder: https://doi.org/10.5281/zenodo.17013378 - Aysha Zummer; Dr. Fozia Akram*; Zuhaa Hassan (`, 2025)
Obsessive–Compulsive Disorder (OCD) is a chronic and debilitating mental health condition that significantly impairs emotional functioning and quality of life (QoL). The present study sought to explore the relationships between emotional empathy, psychological resilience, and quality of life in patients with OCD, along with examining the differences in gender, age, and socioeconomic status (SES) within the sample. Using a standard measure of emotional empathy, psychological resilience, and quality of life (QoL), a sample of N =80 Individuals with OCD was assessed. The descriptive statistics showed a moderate emotional empathy level and a lower-than-average psychological resilience and QoL score in comparison to population benchmarks. Emotional empathy, psychological resilience, and QoL (p < .01) showed significant positive correlation as revealed by Pearson correlation analysis which indicates that emotional empathy and psychological resilience predict QoL. Independent samples t-tests revealed that females performed better than males on empathy, psychological resilience, and QoL, while younger participants outperformed older participants in psychological resilience and QoL. Unmarried individuals scored significantly higher than married individuals on empathy, psychological resilience, and quality of life (QoL) based on the independent samples t-tests. One-way ANOVA further revealed significant differences based on SES, with higher education correlating with greater empathy, psychological resilience, and QoL. These results emphasize the importance of the psycho-social dimensions in the well-being of Individuals with OCD and highlight the need for strong multidimensional approaches that go beyond symptom relief to augment empathy and psychological resilience. Causal relationships and therapeutic implications should be investigated in future studies using longitudinal and interventional frameworks. Keywords: obsessive–compulsive disorder, emotional empathy, psychological resilience, quality of life, gender differences, socioeconomic status